The Sound Horeg Phenomenon: Health Impacts of Infrasound Exposure: A Literature Review - Iwan Setiawan Adji; Nyovita Ayuningrum; Devy Ayu Ningtiyas; Fadli Rizal Faqihudin; Rayhan Fahrezi Al Farghani; Ria Reanita (Newinera Publisher, 2025)
The sound horeg phenomenon represents a cultural practice involving the use of high-power audio systems during social events in various regions of Indonesia, particularly East Java. While it serves as an important medium of entertainment, cultural expression, and local economic activity, exposure to excessive noise dominated by low-frequency noise (LFN) and infrasound raises public health concerns. This literature review aims to evaluate current scientific evidence regarding the biological, neurophysiological, psychological, and social impacts of infrasound exposure on humans. A comprehensive search was conducted in PubMed, Scopus, ScienceDirect, Google Scholar, and ProQuest for articles published between 2015 and 2025. The results show that moderate-intensity infrasound (≤90 dB) causes sleep disturbances, increased stress, and subtle neurological adaptations that can alter long-term cognitive function. Extreme exposure, such as to high-intensity sound (≥120 dB), carries a high risk of causing Noise-Induced Hearing Loss (NIHL), decreased memory function, and social isolation due to communication disorders. In addition to biological effects, psychological factors such as the nocebo effect play a role in the emergence of health complaints due to negative perceptions of loud noise. Therefore, a balance between preserving cultural values and protecting health needs to be achieved through sound intensity regulation, public education, and adaptive acoustic architectural design